Prolactin mediates psychological stress-induced dysfunction of regulatory T cells to facilitate intestinal inflammation. Issue 12 (18th February 2014) - Wu, Wei; Sun, Mingming; Zhang, Huan-Ping; Chen, Tengfei; Wu, Ruijin; Liu, Changqin; Yang, Gui; Geng, Xiao-Rui; Feng, Bai-Sui; Liu, Zhigang; Liu, Zhanju; Yang, Ping-Chang
Abstract : Objective: The dysfunction of immune regulation plays a critical role in the pathogenesis of a number of chronic inflammatory disorders, such as IBD. A close relationship between psychological stress and intestinal inflammation has been noted; the underlying mechanism remains elusive. This study aims to elucidate a pathological pathway between psychological stress and the dysfunction of regulatory T cells (Treg), and its effect on facilitating intestinal inflammation. Design: A restraint stress model was employed to induce psychological stress in mice. The functions of Tregs were determined by assessing the immune suppressor effects in the intestine. A mouse model of intestinal inflammation was established using a low dose of trinitrobenzene sulfonic acid (TNBS) or dextran sulfate sodium (DSS) together with the challenge of chronic stress. Results: After treating mice with restraint stress, the suppressor function of intestinal Treg was compromised, although the frequency of Treg was not changed in the intestine. Further observation revealed that stress induced Tregs in the intestine to differentiate into foxhead box P3 + interleukin (IL)-17 + tumour necrosis factor (TNF)-α + T cells. We also observed that exposure to stress-derived prolactin induced dendritic cells (DC) to produce IL-6 and IL-23 in vitro and in vivo, which played a critical role in altering Treg's phenotypes. Treating mice with chronic stress facilitated the initiation of intestinal inflammation by a low dose of TNBS or DSS, which was abolished by pretreatment with an inhibitor of prolactin, the cabergoline. Conclusions: Psychological stress-derived prolactin alters DC and Treg's properties to contribute to intestinal inflammation.